Association of IL-10 polymorphism with severity of illness in community acquired pneumonia. Issue 2 (1st February 2003) - Gallagher, P M; Lowe, G; Fitzgerald, T; Bella, A; Greene, C M; McElvaney, N G; O'Neill, S J
Abstract : Background: The influence of genetic polymorphisms of interleukin (IL)-10, tumour necrosis factor (TNF)-α, and IL-6 gene promoters on severity of systemic inflammatory response syndrome (SIRS) associated with community acquired pneumonia (CAP) was studied. Methods: Using PCR-RFLP analysis we analysed a −1082G/A single nucleotide polymorphism (SNP) of the anti-inflammatory IL-10 gene, a −308G/A SNP of the pro-inflammatory TNF-α gene and a −174G/C SNP of the IL-6 gene. Illness severity was stratified according to SIRS score, calculated by presence of up to four physiological indices: temperature, white blood cell count, heart rate and respiratory rate (non-SIRS, SIRS 2, SIRS 3, and SIRS 4). Results: A statistically significant stepwise increase in frequency of the IL-10 G allele, associated with higher expression of the gene, was observed in patients with increasing severity of illness from non-SIRS (n=19) to SIRS 2 (n=17), SIRS 3 (n=33) and SIRS 4 (n=24). This was primarily due to a higher frequency of the GG genotype with increasing severity from non-SIRS through to SIRS 4. IL-10 G allele frequency was also increased in patients who died as a result of CAP (n=11) compared with CAP survivors (n=82) (p=0.01). No association was seen between the TNF-α −308G/A and IL-6 −174G/C SNPs and disease. Additionally, no interaction between all three SNP genotypes and disease severity was observed. Conclusions: A polymorphism affecting IL-10 expression may influence the severity of illness in patients with CAP.